Presenting a conceptual framework for an HIV prevention and care continuum and assessing the feasibility of empirical measurement in Estonia: A case study. - Anneli Uusküla (Public Library of Science (PLoS), 2020)
Objective We aim to show the feasibility of using an integrated prevention and care continuum (PCC) model as a complete and improved tool for HIV control measurement and programming. Alignment of prevention and care continua is essential to further improve health outcomes and minimize HIV transmission risk. Design Cross-sectional study. Methods Data from 977 persons who inject drugs (PWID) collected in 2011-2016 in Tallinn, Estonia, were used to construct an HIV PCC for PWID, stratified by risk for acquiring or transmitting HIV infection and by coverage of combined interventions. We also estimated the average protective effect of current levels of intervention provision. Results 74.4%, 20.3% and 35.2% of PWID were currently using needle and syringe programmes (NSP), drug treatment and HIV testing, respectively. 51.1% of current PWID were HIV seropositive and of those 62.5% were currently on ART and 19.0% were virally suppressed. Across the PCC, individuals moved between categories of being aware and ever using drug treatment (resulting in -50% "leakage"); from ever having used to currently using drug treatment (-59%); between "ever testing" and "current (continuous) testing" (-62%); and from self-reported antiretroviral therapy (ART) adherence to viral suppression (-70%). Use of prevention services was higher among those at risk of transmission (HIV positive). The overall reduction in acquisition risk among HIV-negative PWID was 77.7% (95% CrI 67.8-84.5%), estimated by the modelled protective effects of current levels of NSP, drug treatment and ART compared to none of these services. Conclusions Our findings suggest that developing a cohesive model for HIV prevention and treatment is feasible and reflects the bi-directional relationships between prevention and care. The integrated continuum model indicates the major factors which may predict the epidemic course and control response.